Racial Diversity and Racial Policy Preferences: The Great Migration and Civil Rights - Alvaro Calderon; Vasiliki Fouka; Marco Tabellini (Institute of Labor Economics (IZA), 2021)
Between 1940 and 1970, more than 4 million African Americans moved from the South to the North of the United States, during the Second Great Migration. This same period witnessed the struggle and eventual success of the civil rights movement in ending institutionalized racial discrimination. This paper shows that the Great Migration and support for civil rights are causally linked. Predicting Black inflows with a shift-share instrument, we find that the Great Migration increased support for the Democratic Party and encouraged pro-civil rights activism in northern and western counties. These effects were not only driven by Black voters, but also by progressive and working class segments of the white population. We identify the salience of conditions prevailing in the South, measured through increased reporting of southern lynchings in northern newspapers, as a possible channel through which the Great Migration increased whites' support for civil rights. Mirroring the changes in the electorate, non-southern Congress members became more likely to promote civil rights legislation, but also grew increasingly polarized along party lines on racial issues.
Keywords: D72; J15; N92; 330; race; diversity; civil rights; Great Migration